Regional Disparities in Rehabilitation Resources and Service Provision for Older Adults in Secondary Healthcare Regions: Analysis of a Large Health Insurance Claim Database in Japan. - Yamaguchi, Kaori; Nakanishi, Yasuhiro; Nishioka, Yuichi; Imamura, Tomoaki; De Groote, Wouter; Akahane, Manabu (Health Services Insights, 2026)
Background: Regional health disparities have been reported in many countries, including Japan. As rehabilitation needs increase worldwide owing to population aging and the epidemiological shift from communicable to non-communicable diseases, addressing unmet rehabilitation needs is crucial. Objective: To analyze and compare rehabilitation resources and service provision for older adults across secondary healthcare regions in Japan. Design: A quantitative, analytical cross-sectional design was used in this study. Methods: Nara Prefecture, a representative region in Japan comprising five secondary healthcare regions, was selected as the study setting. Data relevant to rehabilitation were obtained from routine national surveys and the Kokuho local government database for the period April 2019 to March 2020, and retrospectively analyzed as secondary data. The Kokuho database includes medical insurance claims for 213,933 residents aged ≥ 75 years, covering the entire prefectural population in this age group. A descriptive regional comparison was conducted using aggregated administrative data, including age-standardized claims ratios for rehabilitation sessions, to compare secondary healthcare regions. Results: The southern secondary healthcare region, characterized by the smallest population and lowest population density, showed distinctive features. It had the lowest per capita number of rehabilitation beds and professionals across all medical institutions within the region among the secondary healthcare regions. Although the proportion of individuals receiving rehabilitation services was the highest, the overall volume of services provided was the lowest, even after adjusting for age and population size. Notably, the provision of outpatient rehabilitation services across all providers within the region was particularly low compared with that in other regions. Conclusions: This study revealed regional disparities in rehabilitation resources and service provision in secondary healthcare regions, highlighting the need for more equitable access. These findings underscore the value of routinely collected administrative and claims data for regional need assessment, particularly for informing evidence-based planning and resource allocation.